2021
DOI: 10.3390/toxins13040260
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Oocytes from Gilts and Sows to Beauvericin and Deoxynivalenol and Its Relationship with Oxidative Stress

Abstract: Beauvericin (BEA) and deoxynivalenol are toxins produced by Fusarium species that can contaminate food and feed. The aim of this study was to assess the effects of these mycotoxins on the maturation of oocytes from gilts and sows. Furthermore, the antioxidant profiles in the oocytes’ environment were assessed. Cumulus-oocyte-complexes (COCs) from gilts and sows were exposed to beauvericin (BEA) or deoxynivalenol (DON) and matured in vitro. As an extra control, these COCs were also exposed to reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Moreover, depending on the developmental stage, oocytes can be more sensitive to mycotoxins. Oocytes from gilts are more susceptible to DON and BEA than those from sows, probably because of a difference in the redox balance [189]. In pigs, the negative impact of DON was previously demonstrated by the inhibition of oocyte maturation [190].…”
Section: In Vitro Experimental Trialsmentioning
confidence: 99%
“…Moreover, depending on the developmental stage, oocytes can be more sensitive to mycotoxins. Oocytes from gilts are more susceptible to DON and BEA than those from sows, probably because of a difference in the redox balance [189]. In pigs, the negative impact of DON was previously demonstrated by the inhibition of oocyte maturation [190].…”
Section: In Vitro Experimental Trialsmentioning
confidence: 99%
“…In the present study, we measured the antioxidant capacity in the serum, liver, and follicular fluid of gilts and found that inclusion of either MC or MW resulted in a significant elevation of MDA and suppressed secretions of SOD, suggesting that oxidative stress was induced by a high level of mycotoxins. Oxidative stress is a phenomenon that occurs in a cell when the concentration of reactive oxygen species exceeds the antioxidant capacity, and it usually impairs the reproductive performance of sows [23]. Luderer et al suggested that oxidative stress was involved in reproductive toxicity caused by various stimuli such as a dietary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with a single mycotoxin, multiple mycotoxins contained in naturally moldy feed have more severe toxicity due to their synergism. However, most studies of the effects of mycotoxins on the growth and development of pigs added a purified mycotoxin to the diet [13,16,[21][22][23], and the hygiene standards in China and the EU for porcine diets were established according to results based on experiments conducted with purified mycotoxin. To date, the dose-dependent effects of including different levels of mycotoxin-contaminated cereal grains on the growth performance and ovarian follicle reserve in replacement gilts is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The other is the non-enzymatic antioxidant system, including thioneine, vitamin C, vitamin E, glutathione, selenium (Se), etc [34]. Oxidative stress impaired many physiological processes of reproductive system, from oocyte maturation and fertilization to pregnancy and embryo development [11,35,36]. Once oxidative stress occurs in granulose cell, it impairs its function.…”
Section: Discussionmentioning
confidence: 99%